Symbolic representation of the number three: a study with three-year-old children from contrasting socioeconomic environments. Issue 6 (17th August 2016) - Martí, Eduardo; Scheuer, Nora; Cavalcante, Silvia; Trench, Máximo; Brizuela, Bárbara M.
ABSTRACT: The goal of the present study was to compare a range of aspects in children's symbolic knowledge about the number three among two groups of three-year-olds from contrasting socioeconomic backgrounds. Every child was presented with five tasks that focused on the number three and that had cognitive demands of different complexity: expressing their age, reciting the conventional number series up to three, quantifying a collection of three, and two tasks requiring the use of visually presented quantitative information.The results showed the same order of difficulty of the tasks in both socioeconomic groups and a clear performance difference depending on socioeconomic background. These findings show that symbolic knowledge about the number three does not come in an all or none fashion. Rather, different aspects of this symbolic competence become apparent in response to different tasks, and seem to depend largely on the socioeconomic environment in which children develop.